Forensics under fire: are bad science and dueling experts corrupting criminal justice? - Fisher, Jim (Rutgers University Press, 2008)
Forensic pathologists from hell : bungled autopsies, bad calls, and blown cases -- A question of credibility : bad reputations and the politics of death -- The sudden infant death debate : how many babies are murdered? -- Infants who can't breathe : illness or suffocation? -- Swollen brains and broken bones : disease or infanticide? -- Fingerprint identification : trouble in paradise -- Fingerprints don't lie : except in Scotland -- Shoe print identification and foot morphology : the lay witness and the Cinderella analysis -- Bite mark identification : do teeth leave prints? -- Earmark identification : emerging science or bad evidence? -- Expert vs. expert : the handwriting wars in the Ramsey case -- The Ramsey case : act two -- Hair and fiber identification : the inexact science -- DNA analysis : backlogs, sloppy work, and unqualified people -- Bullet identification : FBI style -- The celebrity expert : Dr. Henry Lee